Differential Function of Melatonin MT1 and MT2 Receptors in REM and NREM Sleep - Gobbi, Gabriella; Comai, Stefano (Frontiers in Endocrinology, 2019)
The pathophysiological function of the G-protein coupled melatonin MT1 and MT2 receptors has not yet been well clarified. Recent advancements using selective MT1/ MT2 receptor ligands and MT1/MT2 receptor knockout mice have suggested that the activation of the MT1 receptors are mainly implicated in the regulation of rapid eye movement (REM) sleep whereas the MT2 receptors selectively increase non-REM (NREM) sleep. Studies in mutant mice show that MT1 knockout mice have an increase in NREM sleep and decrease in REM sleep, while MT2 knockout mice a decrease in NREM sleep. The localization of MT1 receptors is also distinct from MT2 receptors; for example, MT2 receptors are located in the reticular thalamus (NREM area), while the MT1 receptors in the Locus Coeruleus and lateral hypothalamus (REM areas). Altogether, these findings suggest that these two receptors not only have a very specialized function in sleep, but that they may also modulate opposing effects. These data also suggest that mixed MT1-MT2 receptors ligands are not clinically recommended given their opposite roles in physiological functions, confirmed by the modest effects of melatonin or MT1/MT2 non-selective agonists when used in both preclinical and clinical studies as hypnotic drugs. In sum, MT1 and MT2 receptors have specific role in the modulation of sleep, and consequently, selective ligands with agonist, antagonist, or partial agonist properties could have therapeutic potential for sleep; while the MT2 agonists or partial agonists may be indicated for NREM-related sleep and/or anxiety disorders, the MT1 agonists or partial agonists for REM-related sleep disorders. Furthermore, MT1 but not MT2 receptors seem involved in the regulation of the circadian rhythm. Future research will help further develop MT1 and/or MT2 receptors as target for neuropsychopharmacology drug development.